Preliminary Study of the Third Servant Song of Second Isaiah - WANG, Dong (Journal of Research for Christianity in China (JRCC), 2025)
587 B.C, Jerusalem was conquered by the Babylonians, ending the Kingdom of Judah. It became an unprecedented disaster for the Jewish people in the history of Jews. It aims to study the historical, political and theological situation of Israelites around the period of exile. Since Second Isaiah is full of verses concerning the servant and it has to do with the situation of Israelites at that time, then based on it, it tries to study the third servant song from a holistic perspective. The servant has the responsibility of proclaiming the words of Yahweh among gentiles, according to the creative role that Yahweh played. As a result, the servant’s public identity was questioned by different groups.
Keywords: Exile, Monotheism, Servant, Justice